Moderasi Beragama untuk Mendeteksi Dini Radikalisme di Dunia Pendidikan: : Sebuah Sintesis Konseptual - Rohadi, Tedi; Hendi Hidayat (TSAQAFATUNA : Jurnal Ilmu Pendidikan Islam, 2025)
Religious moderation (wasathiyyah) is increasingly promoted as a counter-narrative to radicalism in pluralistic societies, yet its potential as a theoretical foundation for early detection frameworks in education remains underexplored. This study adopts a conceptual synthesis approach to integrate insights from religious studies, education, and counter-radicalization literature to theorize how moderation values can inform and enhance anticipatory models of radicalization in schools and universities. Through purposive literature selection and thematic coding, four interrelated themes were identified: (1) the foundational values of religious moderation, (2) early indicators of radicalization, (3) the design of moderation-informed detection instruments, and (4) the role of educational institutions as cultivators and detectors of ideological orientation. Visual models were developed to map the conceptual relationships between moderation values, radical indicators, measurement strategies, and institutional mechanisms. The findings suggest that moderation principles such as tawassuth, tasamuh, and i’tidal can be operationalized not only as preventive ethics but also as analytical tools for interpreting ideological shifts before they manifest behaviorally. This study advances a value-sensitive and education-centered framework for early detection, offering a culturally grounded alternative to securitized models. It concludes by recommending future empirical research to validate and adapt the proposed framework in diverse educational contexts, particularly within Muslim-majority settings.